UTILIZATION OF ARTIFICIAL INTELLIGENCE TECHNOLOGY IN CLASS MANAGEMENT: POTENTIAL AND CHALLENGES FROM A LITERATURE STUDY PERSPECTIVE - Latipah, Euis; Latipah, Evi Nur; Akhfas, Muhammad Imam; Rahmatillah, Nursida (Academic Solution Publisher, 2025)
Artificial Intelligence (AI) has emerged as a significant innovation in education, particularly in classroom management. This study aims to explore the potential and challenges of AI implementation through a literature review approach. Data were collected from reputable academic journals and research reports. The findings reveal that AI can support teachers by reducing administrative burdens, providing interactive learning media, and promoting student learning autonomy. However, the use of AI also faces several obstacles, such as limited infrastructure, lack of teacher training, and the risk of overreliance on technology, which may reduce the humanistic aspect of education. Therefore, AI implementation must be designed thoughtfully to uphold student-centered educational values.